2023
DOI: 10.3390/plants12183288
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon Rind Mediated Biosynthesis of Bimetallic Selenium-Silver Nanoparticles: Characterization, Antimicrobial and Anticancer Activities

Amr Hashem,
Gharieb El-Sayyad,
Abdulaziz Al-Askar
et al.

Abstract: One of the most hazardous diseases that influences human health globally is microbial infection. Therefore, bimetallic nanoparticles have received much attention for controlling microbial infections in the current decade. In the present study, bimetallic selenium–silver nanoparticles (Se-Ag NPs) were effectively biosynthesized using watermelon rind WR extract through the green technique for the first time. UV-visible spectroscopy, transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…04-0783. The obtained peaks at the 2θ value confirmed that the synthesized AgNPs possess a face-centered cubic (fcc) structure 77 . The average crystallite size of the nanoparticles was calculated from the full-width half maximum and Bragg reflections by using the following Debye–Scherrer equation 78 : where D is the crystal size estimated from the XRD patterns, θ is the Bragg angle in degrees, λ is 1.5406 Å, the wavelength of the X-ray source used, β is the full-width half maximum (FWHM) of the diffraction peak in radians and K is the constant (geometric factor) of Debye–Scherrer’s equation.…”
Section: Resultssupporting
confidence: 52%
“…04-0783. The obtained peaks at the 2θ value confirmed that the synthesized AgNPs possess a face-centered cubic (fcc) structure 77 . The average crystallite size of the nanoparticles was calculated from the full-width half maximum and Bragg reflections by using the following Debye–Scherrer equation 78 : where D is the crystal size estimated from the XRD patterns, θ is the Bragg angle in degrees, λ is 1.5406 Å, the wavelength of the X-ray source used, β is the full-width half maximum (FWHM) of the diffraction peak in radians and K is the constant (geometric factor) of Debye–Scherrer’s equation.…”
Section: Resultssupporting
confidence: 52%
“…UV–Vis analysis was carried out to measure absorbance between 300 and 800 nm using a UV–Vis spectrophotometer (JENWAY 6305 spectrophotometer). The size and shape of Ag-NPs were characterized using transmission electron microscopy (TEM) (JEM1230, Japan, Akishima, Tokyo, 196–8558) ( Hashem et al, 2023b ). SEM–EDX was used to analyze the elemental compositions of Ag-NPs produced during biosynthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticles (having size in range of 100 nm) have received significant attention due to the unique physical and chemical properties that arise primarily from their dimensions. These properties make them suitable in a broad array of applications ( Hashem and Salem, 2022 ; Hashem et al, 2023 ) including gas sensors ( Shin et al, 2023 ), lithium-ion batteries ( Fang et al, 2023 ), dye-sensitized solar cells ( Jin et al, 2023 ), adsorption ( Debnath and Das, 2023 ), heterogeneous photodegradation ( Mota et al, 2023 ), biosensing ( Lei et al, 2023 ), and antibacterial substrates ( lashin et al, 2023 ; Al-Askar et al, 2023 ). Additionally, NPs have shown a vast range of biological applications, including antibacterial, anticancer, and antioxidant properties ( Singh et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%